Sedimentation analysis at the mouth of the Dique Channel to the Cartagena Bay through hydrographic surveys - Rojas Macías, Harold; Martinez, Octavio Martinez; Monterroza Pantoja, Marjohnny (The International Hydrographic Review, 2025)
This article demonstrates the problem currently facing Cartagena Bay due to excessive sedimentation at the mouth of the Dique Channel, based on the analysis carried out by the Hydrographers of the National Hydrographic Service taking advantage of the management of the different seabed research technologies available to the Caribbean Oceanographic and Hydrographic Research Center (CIOH). Between December 2022 and January 2023, a hydrographic survey was carried out at the mouth of the Dique Channel, carrying out a multitemporal analysis with the hydrographic data from 2012 and 2020 stored in the hydrographic database, allowing a clear identification of the volume of the sedimentation rate in this important area of Cartagena Bay. The article shows the need for high monitoring of the study area by the National Maritime Authority, also because the port of Cartagena is one of the most important in Colombia.